Address to the Historical Society of South Africa on the occasion of its tenth anniversary (Historia, 2021)
I should like to thank you for your kind invitation to be here with you this morning on the occasion of the tenth anniversary of the Historical Society. And, it is my first duty to congratulate you on your "birthday" and to wish the Society all good wishes for its growth from stre~gth to strength in the future. I am aware it was founded ten years ago in an effort to encourage the study of history, particularly in the schools, as it was feared that there was a waning interest in the subject at school level; over the years the Society has aimed at stimulating a live and vital interest in the subject and has hoped that this interest would encourage a greater number of pupils to follow it and to know more about the past and the traditions of this country of ours. It has issued its regular publications; these have been brought into the schools; and as a result it has succeed~d in bringing many little-known facts and information about our past to the knowledge of the teachers of history in the schools. So, on this occasion of its tenth anniversary, the Association has every reason to be proud of what it has already achieved, and it is with pleasure that I felicitate you at this juncture. I feel it is an honour to say a few words to you on this occasion, despite the fact that I am fully conscious that there are many more and better qualified to do so.
Keywords: History teaching; History; History in Schools